Aristolochia versicolor S.M. Hwang (Aristolochiaceae), a new record for the flora of Vietnam - Van Truong Do; Thi Thao Hoang (Vietnam Journal of Science, Technology and Engineering, 2022)
With over 600 species, the genus Aristolochia L. (Aristolochiaceae) is extensively spread in temperate, subtropical, and tropical climates. Numerous Aristolochia species are significant host plants for the Papilionidae family of butterflies and are regarded as a key group to research the relationship between plants and butterflies. Moreover, traditional Chinese and Vietnamese medicine frequently use a few Aristolochia species. Aristolochia biodiversity hotspots are found in southern China and northern Vietnam. There are currently 25 Aristolochia species recognized from Vietnam. We just gathered some intriguing Aristolochia specimens in northern Vietnam’s protected forests while updating the taxonomy of the species. After a thorough analysis of the specimens and comparisons with the protologue and type specimens of previously identified Siphisia species, it was determined that the specimens perfectly matched A. versicolor S.M. Hwang, a medicinal plant that was previously identified. As a result, A. versicoloris now listed as a new record for Vietnam’s flora. The description of the morphology, color images, iconography, distribution, phenology and habitat, state of conservation, and comparison with other morphologically are provided.